HEPATITIS-A QUICK VIEW - Rashida Parveen; Kanwal Ashiq; Mayyda Asif Bajwa; Mehwish Qayyum (International Journal of Pharmacy & Integrated Health Sciences)
Viral Hepatitis Every one of us has heard the word “hepatitis” and considered it a fatal disease. “Viral hepatitis” is the inflammation of the liver that is caused by a nasty family of viruses. Due to hepatitis, it is estimated that globally 1.34 million people died per year and it is also reported that about 80% of cases of liver cancer are only caused by hepatitis B and Hepatitis C together. The number of patients having this infection is amplifying each year, which is quite an alarming situation (1).